Highly conductive graphene@phosphotungstic acid nanocomposite for sensitive electrochemical detection of acetaminophen based on analysis induction strategy in foods - Ruiyu He; Jingjie Zhang; Shixin Li; Yuzhen Yang; Yaru Xu; Zhixiang Xu; Yufeng Sun (Food Chemistry Advances)
In this work, an electrochemical sensing platform based on graphene@phosphotungstic acid nanocomposite (GR@PWA) was constructed for sensitive determination of acetaminophen (AP). The electrochemical performance of the obtained sensor (GR@PWA/GCE) was investigated by cyclic voltammetry, differential pulse voltammetry and electrochemical impedance spectroscopy. The calculated effective active area of GR@PWA/GCE was 2.22 times than that of bare glassy carbon electrode. Under the optimal conditions, a good linear relationship with AP concentration ranging from 1 μM to 100 μM and a lower limit of detection (0.305 μM) were obtained. The proposed sensing platform exhibited excellent anti-interference capability, repeatability, reproducibility and stability. Furthermore, the beef and lamb samples were employed to perform recovery test with a satisfactory recovery rate (88.0 %-107.6 %). The content of AP in pork and chicken samples was detected by the proposed sensor and high performance liquid chromatography. The results of the two methods were compared, and no significant difference was found (P > 0.05). This analysis strategy provides a basis for further expanding the application of electrochemical sensors in food safety detection.